Whole-Genome Methylation Sequencing Analysis and Functional Verification of LIM-Homeobox Family Genes in Cervical Cancer - Yu R; Yu Q; Shi J; Meng X; Deng Z; Suo J; Yang H (International Journal of General Medicine)
Rong Yu,1,* Qin Yu,1,* Jie Shi,2,* Xue Meng,3 Zhiyuan Deng,3 Jing Suo,4 Hao Yang1 1Department of Radiation Oncology, Peking University Cancer Hospital (Inner Mongolia Campus) & Affiliated Cancer Hospital of Inner Mongolia Medical University, Huhhot, Inner Mongolia Autonomous Region, 010020, People’s Republic of China; 2Department of Gynecology and Oncology, Peking University Cancer Hospital (Inner Mongolia Campus) & Affiliated Cancer Hospital of Inner Mongolia Medical University, Huhhot, Inner Mongolia Autonomous Region, 010020, People’s Republic of China; 3Department of Graduate School, Inner Mongolia Medical University, Hohhot, Inner Mongolia Autonomous Region, 010059, People’s Republic of China; 4Department of Gynecology and Obstetrics, the Affiliated Hospital of Inner Mongolia Medical University, Hohhot, Inner Mongolia Autonomous Region, 010050, China*These authors contributed equally to this workCorrespondence: Hao Yang, Department of Radiation Oncology, Peking University Cancer Hospital (Inner Mongolia Campus) & Affiliated Cancer Hospital of Inner Mongolia Medical University, No. 42, Zhao Wu Da Road, Huhhot, Inner Mongolia Autonomous Region, 010020, People’s Republic of China, Tel +86 471-3280801, Email hdgeu98@163.com Jing Suo, Department of Gynecology and Oncology, Affiliated People’s Hospital of Inner Mongolia Medical University, 1 Tongdao North Street, Hohhot, Inner Mongolia Autonomous Region, 010050, People’s Republic of China, Tel +86 471-3451350, Email suojing49@sina.comBackground: Gene methylation in cells is an important factor in tumorigenesis, and radiotherapy can change DNA methylation in cells. In this study, complete genome methylation sequencing (BS-Seq) technology was used to analyze the genome-wide methylation of patients with cervical cancer before and after radiotherapy.Methods: Three pairs of cervical squamous cell carcinoma samples were collected from patients before and after radiotherapy in July 2020. Genome-wide DNA methylation profiles were generated using WGBS. Bioinformatics analysis was conducted to identify differential methylation regions (DMRs) and their associated genes and pathways. The study focused on the methylation changes of LHX2, LHX5, and LHX9 genes, assessing their expression levels using qRT-PCR and correlating these changes with cervical cancer stages.Results: MCG was the main way of genomic DNA methylation in the three patients. The DNA methylation level and methylation density on each chromosome varied greatly. As revealed by comparison of methylation before and after radiation in the three patients, 1287, 1261 and 789 differential methylation genes were identified, respectively.  3) Combined with clinical treatment, methylation level difference and correlation enrichment analysis, it was found that LHX2, LHX5 and LHX9 were closely related to the occurrence and development of cervical cancer. After 5-Aza-DC and radiotherapy, the methylation of the CpG islands in LHX2, LHX5 and LHX9 genes in these patients was decreased (p < 0.01), and the mRNA and protein expression levels were relatively increased (p < 0.01).Conclusion: In our present work, genome-wide DNA methylation maps of cervical cancer tissues before and after radiotherapy were successfully constructed. We found that LHX5 and LHX9 genes are closely related to cervical cancer. LHX5 and LHX9 have a negative effect on cervical cancer. The migration ability of LHX9 silenced cells was significantly enhanced after irradiation.Keywords: cervical cancer, radiation therapy, whole-genome bisulfite sequencing, WGBS, LHX2, LHX5, LHX9